KED-AES algorithm: combined key encryption decryption and advance encryption standard algorithm - Edwin Romeroso Arboleda; Carla Eunice R. Fenomeno; Joshua Z. Jimenez (Institute of Advanced Engineering and Science, 2019)
Two existing cryptosystems are being combined and proposed. It is the enhanced combination of KED (Key Encryption Decryption), a cryptosystem that uses modulo 69 and the AES (Advance Encryption Standard) cryptography. The strength of the KED is that the keys are being used by the sender and the receiving end. The AES is easy to implement and has good defense against various attacks such as hacking.